MONTAGEM DE BIOGRAFIAS EM MIRANDA JULY - Baschirotto, Viviane (2016)
Miranda July tells many stories, when producing a film, writing a book or through her visual works. The artist makes up biographies or readapts them, assembling and collecting memories, just like Aby Warburg and Walter Benjamin have done with art history, a knowledge montage. The text approach the series of sculptures Eleven heavy things, the unusual situations and reactions that produces and how the works can be thought of as an autobiographical search. It also about the work It chooses you where the artist makes a collection of memories with interviews to ordinary people, creating a constellation of dialogues, a montage biographies.